Вплив сухого екстракту з трави герані болотної на показники системи гемостазу = The effect of dry extract of geranium palustre herb on indicators of gemostasis - Ostapets, M. O.; Shevtsov, I. I.; Bereznyakova, M. E.; Karabut, L. V. (Journal of Education, Health and Sport, 2015)
Ostapets M. O., Shevtsov I. I., Bereznyakova M. E., Karabut L. V. Вплив сухого екстракту з трави герані болотної на показники системи гемостазу = The effect of dry extract of geranium palustre herb on indicators of gemostasis. Journal of Education, Health and Sport. 2015;5(10):244-250. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.32828 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2810%29%3A244-250 https://pbn.nauka.gov.pl/works/663165 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2015. Revised 05.09.2015. Accepted: 20.10.2015. УДК 615.322:582.751:615.273 ВПЛИВ СУХОГО ЕКСТРАКТУ З ТРАВИ ГЕРАНІ БОЛОТНОЇ НА ПОКАЗНИКИ СИСТЕМИ ГЕМОСТАЗУ THE EFFECT OF DRY EXTRACT OF GERANIUM PALUSTRE HERB ON INDICATORS OF GEMOSTASIS М. О. Остапець, І. І. Шевцов, М. Є. Березнякова, Л. В. Карабут M. O. Ostapets, I. I. Shevtsov, M. E. Bereznyakova, L. V. Karabut Національний фармацевтичний університет, Харків, Україна National University of Pharmacy, Kharkiv, Ukraine Abstract The article devided to studying the indicators of hemostasis during introduction of dry extract from Geranium Palustre herb. Established that the investigation extract in its composition contains the active platelet components. Into the studying parameters of coagulation hemostasis the dry extract from Geranium Palustre herb was showed an active effect on the activation of «internal» mechanism of blood clotting – I phase (formation of prothrombinase), moderately affected on the II and III stages. In the studying of anticoagulant system and fibrinolysis was revealed that the investigated extract was showed a low antifibrynolityc action and not affected on the anticoagulant mechanism. High hemostatic activity of dry extract from Geranium Palustre herb can be explained by the presence of biologically active substances in the extract. Keywords: hemostasis, coagulation, dry extract from Geranium Palustre herb. Реферат Стаття присвячена дослідженню показників системи гемостазу на фоні введення сухого екстракту з трави герані болотної. Встановлено, що досліджуваний екстракт в своєму складі містить активний тромбоцитарний компонент. При вивченні показників коагуляційного гемостазу сухий екстракт з трави герані болотної проявив активний вплив на активацію «внутрішнього» механізму зсідання крові – I фазу (утворення протромбінази), помірно впливав на II та III стадії. При дослідженні системи антизсідання та фібринолізу встановлено, що досліджуваний екстракт проявив слабку антифібринолітичну дію та не впливав на антикоагулянтну ланку гемокоагуляції. Висока гемостатична активність сухого екстракту з трави герані болотної може пояснюватися наявністю біологічно активних речовин у складі екстракту. Ключові слова: гемостаз, коагуляція, сухий екстракт з трави герані болотної. Реферат ВЛИЯНИЕ СУХОГО ЭКСТРАКТА ИЗ ТРАВЫ ГЕРАНИ БОЛОТНОЙ НА ПОКАЗАТЕЛИ СИСТЕМЫ ГЕМОСТАЗА. Статья посвящена исследованию показателей системы гемостаза на фоне введения сухого экстракта из травы герани болотной. Установлено, что исследуемый экстракт в своем составе содержит активный тромбоцитарный компонент. При изучении показателей коагуляционного гемостаза сухой экстракт из травы герани болотной проявил активное влияние на активацию «внутреннего» механизма свертывания крови – I фазу (образование протромбиназы), умеренно влиял на II и III стадии. При исследовании системы противосвертывания и фибринолиза установлено, что исследуемый экстракт проявил слабое антифибринолитическое действие и не влиял на антикоагулянтное звено гемокоагуляции. Высокая гемостатическая активность сухого экстракта травы герани болотной может объясняться наличием биологически активных веществ в составе экстракта. Ключевые слова: гемостаз, коагуляция, сухой экстракт из травы герани болотной.